Identification and Angular Distribution of Residual Radionuclides Detected on the Wall of BATAN’s Cyclotron Cave - I. Kambali; H. Suryanto; P Parwanto (Atom Indonesia, 2016)
Detection and measurement of radiation sources around BATAN’s cyclotron facilities in Serpong are required as an early step to avoid radiation impacts on the radiation employees who work with the cyclotron. In this paper, radiation emitted from the wall of the CS-30 cyclotron cave are detected and measured using an NaI(Tl) detector coupled with a pocket multichannel analyzer (MCA) at a counting time of 30 minutes for each sampling point on the wall. The sampling points were in the directions of within ±150o with respect to the incoming proton beams, and the measurements were conducted at heights between 1.2 m and 1.8 m off the floor for every sampling point. The experimental results indicate that Co-60 and Cs-134 detected on the cyclotron cave wall are major radionuclides that contribute to the emitted gamma radiation. The distribution of the gamma ray intensities given off by Co-60 and Cs-134 depend on the angle and position of the sampling points. In general the highest gamma ray rates can be found in the area around 0o relative to the incoming proton beams. In addition, no other radioactive sources are significantly detected on the wall. The maximum exposure measured on the wall surface was much less than the permissible occupational exposure for radiation workers and general public.Received: 27 March 2015; Revised: 30 September 2015; Accepted: 15 December 2015